Opportunity, Challenge, and Strategy of Media in Increasing Waqf Literacy: Correlation and Thematic Interpretation of Relevant Quranic Verses: Peluang, Tantangan, dan Strategi Media dalam Meningkatkan Literasi Wakaf: Korelasi dan Interpretasi Tematik Ayat Al-Qur’an yang Relevan - Azwar, Azwar; Achmad Abubakar; Muhammad Irham (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2025)
This study aims to analyze the role of media in enhancing waqf literacy in Indonesia by identifying the opportunities, challenges, and strategies that can be implemented through the integration of thematic interpretations of relevant Quranic verses. This research employs content analysis and thematic interpretation methods to examine the Quranic verses relevant to the research topic. Data are collected from various literature sources, focusing on verses related to charity and waqf, as well as studies concerning media that enhance public understanding of waqf. The results indicate that both mass and digital media play a significant role in improving waqf literacy through strategic information dissemination tailored to audience characteristics. The use of modern technology, collaboration with waqf institutions and religious communities, and real-time analytics present substantial opportunities to broaden public understanding of waqf. However, challenges include a lack of in-depth understanding of waqf among journalists, competition with sensational content on social media, and resource limitations. Effective strategies that can be implemented include the development of engaging educational content, strategic collaborations, multi-channel approaches, and training for journalists.